2-Naphthalenemethanol participates in metabolic activation of 2-methylnaphthalene. (3rd April 2022) - Li, Kunna; Zou, Ying; Wang, Yang; Zhou, Mengyue; Li, Jing; Tan, Rong; Zhang, Shiyu; Li, Weiwei; Zheng, Jiang
Abstract: 2-Methylnaphthalene (2-MN) is an environmental pollutant. Studies have shown that 2-MN is teratogenic, carcinogenic, and cytotoxic. However, the mechanisms of 2-MN induced toxicities remain unclear. This study aimed to characterise reactive metabolites of 2-MN, to define the metabolic pathway, and to determine the enzymes participating in the metabolic activation. A hydroxylation metabolite of 2-MN, 2-naphthalenemethanol (2-NM), was observed in 2-MN-containing mouse liver microsomes. A glutathione (GSH) conjugate was detected in mouse S9 incubations fortified with 2-MN and GSH. A GSH conjugate and an NAC conjugate were found in mouse liver and urine, respectively, in animals given 2-MN. Hepatic protein covalent binding derived from 2-NM was observed in animals administered 2-MN. Cytochrome P450 enzymes and sulfotransferases participated in the metabolic activation of 2-MN.